A NEW GENUS AND REVISION OF KNOWN SPECIES OF EARLY KAZANIAN (UPPER PERMIAN) TEREBRATULIDS FROM THE EASTERN RUSSIAN PLATFORM - Smirnova T.N. (My University, 2004)
The species composition of the genus Dielasma, which has until recently included the majority of Late Permian terebratulids, is revised. The internal structure of some terebratulid species is studied in a series of transverse polished sections. Among these species, only D. kirillowense has appeared to be a true Dielasma in the modern sense. New terebratulid taxa from the eastern Russian Platform are designated: a genus, Campbellelasma, and species C. variiforme, C. vulgaris, and Dielasma robustum.
Keywords: terebratulids; Paleozoic::Permian; Палеозой::Пермская